Strategies for Implementing Human Resource Ethics to Create a Harmonious School Climate at Madrasah Tsanawiyah - Mesiono Mesiono; Toninasution Toninasution; Fatimah Nayla Zaskia Siregar; Muhammad Amada; Febriani Rambe; Salisa Afany; Sultan Kemala Agung Lubis; Rieke Widyas Putri; Sabila Aghnia Fawwaz; Ahmad Fauzan Shidiq Nasution (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the implementation of human resource (HR) ethics and the strategies employed to create a harmonious school climate at Madrasah Tsanawiyah Negeri (MTsN) 2 Medan. This research used a descriptive qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation involving the principal, vice principal, teachers, educational staff, and students as research informants. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing and verification. The validity of the data was ensured through source, technique, and time triangulation. The findings indicate that the implementation of HR ethics at MTsN 2 Medan has been carried out effectively and is reflected in values such as discipline, responsibility, honesty, professionalism, cooperation, and mutual respect among all members of the school community. The strategies implemented include exemplary leadership by the principal, the integration of ethical values into school culture, the strengthening of open and effective communication, the enforcement of discipline, and the continuous development of human resource professionalism. Supporting factors include strong leadership, a religious school culture, harmonious communication, and the competence of teachers and educational staff. Meanwhile, inhibiting factors include differences in individual characteristics, uneven levels of discipline, limited coordination time, and challenges related to technological adaptation. The study concludes that the consistent implementation of HR ethics contributes significantly to the creation of a harmonious school climate characterized by positive working relationships, effective communication, improved discipline, and a safe, comfortable, and conducive learning environment